Giving Women a Bigger Voice in Rural China - Fernandes, Patricia (World Bank, Washington, DC, 2012)
The Poor Rural Communities Development Project (PRCDP) is a rural development intervention covering some of the poorest communities in Guangxi, Sichuan, and Yunnan provinces in China. The project, which is led by the Chinese provincial and county project offices (PMO), reaches out to ethnic minority communities, usually in remote villages, and provides sub grants for basic infrastructure and loans for livelihood improvements. The project involves farmers in important decisions about which kinds of activities will be implemented, and aims to ensure participation of both men and women in project design, implementation, and evaluation. Community members are brought together for discussions facilitated by the project team to talk about key challenges facing the community and to make sure that both women's and men's priorities are heard when it comes to deciding how village funds will be used. This smart lesson describes how a simple 'gender mainstreaming' approach was effectively adopted in targeted villages in rural China and highlighting the different ways men and women understand community priorities.